VRTOOL the virtual reality modeling language integrating tool - Alba, Ma Margarita C. (1998)
The Philippine National Museum is the symbolic integration of the Philippine culture and arts. It is the guardian of the treasures of the Filipino people. It presents the timeless masterpieces of our national artists, the beauty of the antiquity in its entire splendor and more. Unfortunately, all this wealth is contained deep within the walls of the museum, unreachable from the hands of some people who would want to learn about the Filipinos. How do we present the Filipino heritage to the worldn Virtual Reality and the Internet, two big concepts dominating this information technology age. The onset of virtual reality into the limelight was inevitable. The continous development of computer technology enabled the creation of more realistic and accurate representations of real world objects in the computer. The influence of the Internet is more on the worldwide scale. It has dramatically changed the motion of global communication, as we know it. Access to information of any kind is boundless. The Net has brought the world's inhabitants closer together. To get the maximum benefits from these two areas in computer science, naturally, they would be combined. From this premise, a standard of implementing virtual worlds in the Internet, the Virtual Reality Modeling Language (VRML), was born. One perfect VRML application would be the depiction of the Philippine National Museum.